Nursing workload for cancer patients under palliative care - Patrícia dos Santos Claro Fuly; Livia Márcia Vidal Pires; Claudia Quinto Santos de Souza; Beatriz Guitton Renaud Baptista de Oliveira; Katia Grillo Padilha
Abstract OBJECTIVE To verify the nursing workload required by cancer patients undergoing palliative care and possible associations between the demographic and clinical characteristics of the patients and the nursing workload. METHOD This is a quantitative, cross-sectional, prospective study developed in the Connective Bone Tissue (TOC) clinics of Unit II of the Brazilian National Cancer Institute José Alencar Gomes da Silva with patients undergoing palliative care. RESULTS Analysis of 197 measures of the Nursing Activities Score (NAS) revealed a mean score of 43.09% and an association between the performance status of patients undergoing palliative care and the mean NAS scores. The results of the study point to the need to resize the team of the unit. CONCLUSION The NAS has proven to be a useful tool in oncologic clinical units for patients undergoing palliative care.